KEANEKARAGAMAN JENIS BENALU PARASIT PADA TANAMAN KOLEKSI DI KEBUN RAYA EKA KARYA, BALI - Tahan Uji; Sunaryo Sunaryo; Erlin Rachman (The East Java Biological Society, 2007)
Benalu is one of the parasitic plants which have ataccked many collection plants species in Eka Karya Botanical Garden, Bali. Exploration and collection of these parasitic plants in this area are conducted. Four parasitic plants species, i.e. Dendrophthoe pentandra, Helixanthera cylindrica, Scurrula atropurpurea, and S. parasitica are recorded and they attack 32 collection plants species in Eka Karya Botanical Garden. Dendrophthoe pentandra is reported as the highest population species to parasiting collection plants species. While the Myrtaceae family and Syzygium genera are also reported as the highest parasited species.